DATA FORENSIK DIGITAL DALAM PENYIDIKAN KEJAHATAN BERBASIS TEKNOLOGI PERSPEKTIF HUKUM PIDANA - ARFIN, ZAIN; Seto Aji, Pandam Bayu (Bapelitbang Kabupaten Batang, 2025)
Digital evidence is one of the means of evidence that provides clues to investigations regarding evidentiary issues related to the validity, authenticity, and integrity of digital evidence, so that it can be trusted and recognized as valid evidence in court. Digital forensics is part of the investigation in the application of technology-based science adapted to current developments. The research focus is more specifically descriptive and uses an empirical legal analysis approach in examining the law. This research is also referred to as doctrinal legal research based on literature. The use of digital forensic data is part of the interests of modern science as the development of Industry 5.0 and strengthens the findings of technology-based evidence by providing clarity and objectivity not found in physical evidence. Optimizing the use of personal data as a form of achieving the protection of community rights, providing certified resources and adequate infrastructure. Developing technology to address applicable legal issues in professional resolution. The urgency of digital forensic evidence in the spread of crime in every sector is becoming important, restoring public trust is necessary due to digital developments and preventative efforts regarding the spread of crime.